Alterations of the bacterial ocular surface microbiome are found in both eyes of horses with unilateral ulcerative keratitis. - Martha E Julien; Johnathan B Shih; Bruna Correa Lopes; Lucien V Vallone; Jan S Suchodolski; Rachel Pilla; Erin M Scott (PLoS ONE, 2023)
Next generation sequencing (NGS) studies in healthy equine eyes have shown a more diverse ocular surface microbiota compared to culture-based techniques. This study aimed to compare the bacterial ocular surface microbiota in both eyes of horses with unilateral ulcerative keratitis (UK) with controls free of ocular disease. Conjunctival swabs were obtained from both ulcerated eyes and unaffected eyes of 15 client-owned horses with unilateral UK following informed consent, as well as from one eye of 15 healthy horses. Genomic DNA was extracted from the swabs and sequenced on an Illumina platform using primers that target the V4 region of bacterial 16S rRNA. Data were analyzed using Quantitative Insights Into Molecular Ecology (QIIME2). The ocular surface of ulcerated eyes had significantly decreased species richness compared with unaffected fellow eyes (Chao1 q = 0.045, Observed ASVs p = 0.045) with no differences in evenness of species (Shannon q = 0.135). Bacterial community structure was significantly different between either eye of horses with UK and controls (unweighted UniFrac: control vs. unaffected, p = 0.03; control vs. ulcerated, p = 0.003; unaffected vs. ulcerated, p = 0.016). Relative abundance of the gram-positive taxonomic class, Bacilli, was significantly increased in ulcerated eyes compared with controls (q = 0.004). Relative abundance of the taxonomic family Staphylococcaceae was significantly increased in ulcerated and unaffected eyes compared with controls (q = 0.030). The results suggest the occurrence of dysbiosis in infected eyes and reveal alterations in beta diversity and taxa of unaffected fellow eyes. Further investigations are necessary to better understand the role of the microbiome in the pathophysiology of ocular surface disease.